Academic Culture in Indonesia and Philippines through the Lens of Indonesian EFL Student Exchanges - Syahputri, Imaniar; Nurfaidah, Sitti; Faridawati, Faridawati; Tanghal, Analiza B (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This study explores the academic experiences of Indonesian EFL students participating in an exchange program at a private university in the Philippines. Using a phenomenological approach, this study examines how students adapt to differences in instructional methods, assessment styles, and collaborative learning practices. Findings reveal that Indonesian students initially struggle with the transition from a teacher-centered learning environment to a student-centered approach that emphasizes active participation. Frequent quizzes and formative assessments at the host institution contrast with the summative evaluation methods in Indonesia, requiring them to adjust their study habits. The shift from independent to group-based research assignments challenges their accustomed academic behaviors but enhances teamwork and problem-solving skills. This study implies the need for pre-departure training programs to better prepare exchange students for academic cultural differences.